Analysis method of software failure modes in command information system based on complex networks - WANG Bo, JIANG Xuping, JING Huiqian (Zhihui kongzhi yu fangzhen)
The command information system software forms a network through sophisticated interactions, where a single software failure can widely propagate within the network and cause severe consequences. Based on a weighted undirected connected graph, this paper constructs a static model of the complex network for the command information system software, proposes a hierarchical centrality algorithm for the multi-layer neighbor influence of nodes, realizes the prediction of software network fault sources, and mines the fault propagation path based on the ant colony system algorithm. Through simulation experiments analyzing the fault mode of a certain command information system software, the effectiveness of the proposed method is verified.